SEASONAL DYNAMICS OF MACROALGAL COMMUNITIES IN THE PRETO RIVER BASIN, SAO-PAULO, SOUTHEASTERN BRAZIL - Necchi, O.; Pascoaloto, D. (E Schweizerbart'sche Verlags, 1993)
Macroalgal seasonality was analyzed in nine stream segments of the Preto River basin: five of these were sampled monthly for one year and four bimonthly during two years. Seasonal variation of macroalgae was correlated with stream variables (temperature, current velocity, specific conductance, turbidity, surface light, pH and oxygen). Multiple linear regression was applied to evaluate the macroalgal seasonal variability determined by a combination of temperature, current velocity and turbidity, the most influential environmental parameters on macroalgal seasonality. Most species revealed a clear seasonal trend, such that late fall through early spring was the period with highest macroalgal abundance in most sites. Temperature, current velocity and turbidity account for 24 to 83 % of macroalgal species number variation and 24 to 79 % of macroalgal abundance in the basin. The results suggest that the seasonal flow determined by the precipitation regime associated with turbidity and temperature were the major factors influencing the seasonal dynamics of macroalgal communities. The highest values of macroalgal species number and abundance were found under cooler temperatures, lower current velocities and lower values of turbidity.